The Development of Arabic Language Teaching Materials Based on Archipelago Folklore: Service at The Malaysian Institute of Teacher Education - Al Farisi, Mohammad Zaka; Nurmala, Mia; Sauri, Sofyan; Nurbayan, Yayan; Ali, Mad; Supriadi, Rinaldi; Fuadi, Farhan (TAAWUN, 2025)
This community service aims to improve students’ understanding of Arabic language learning by integrating local folklore as a learning medium. This program is implemented by the Arabic Language Education Study Program FPBS UPI in collaboration with the Malaysian Teacher Education Institute (IPG). The methods used include focus group discussions and ethnographic approaches to explore students’ needs and adapt folklore from the origins of Bandung City into teaching materials. The results of the community service show that the use of folklore not only improves students’ understanding of Arabic vocabulary and structure but also enriches their insight into local culture. The impact of this program is seen in the increasing involvement of students in the learning process and the creation of more contextual and relevant learning. This culture-based approach provides an innovative alternative in foreign language learning oriented towards society’s benefit.